RANCANG BANGUN APLIKASI E-PEDOMAN AKADEMIK STMIK PALANGKARAYA BERBASIS ANDROID: Design and Build an Android-Based STMIK Palangkaraya Academic Guideline Application - Haris, Ferdiyani; Rudini, Rudini (Jurnal Sains Komputer dan Teknologi Informasi, 2023)
So far, you can get the STMIK Palangkaraya academic guidebook in 2 (two) ways, namely the printed version and the digital version which can be downloaded from the STMIK Palangkaraya website. The problem for both methods is that for the printed version, the institution needs to budget funds for the printing process. Meanwhile for the e-book version, even though students can easily access the e-book, they need to download it first so they can open the e-book. Therefore it is necessary to design and build an Android-based STMIK Palangkaraya academic guide e-application that can be opened and read anytime and anywhere. Prototyping modeling is applied as a software development method to be built. System design by adopting the Unified Modeling Language (UML). The system that is built will be the academic guidance material for STMIK Palangkaraya Students/I in the process of implementing lectures and the process of Academic Administration